Genome Informatics 2009:Genome Informatics Series Vol. 23 - Shinichi Morishita (Genome Informatics Series, 2009)
This volume contains papers presented at the 20th International Conference on Genome Informatics (GIW 2009) held at the Pacifico Yokohama, Japan from December 14 to 16, 2009. The GIW Series provides an international forum for the presentation and discussion of original research papers on all aspects of bioinformatics, computational biology and systems biology. Its scope includes biological sequence analysis, protein structure prediction, genetic regulatory networks, bioinformatic algorithms, comparative genomics, and biomolecular data integration and analysis. Boasting a history of 20 years, GIW is the longest-running international bioinformatics conference. A total of 18 contributed papers were selected for presentation at GIW 2009 and for inclusion in this book. In addition, this book contains abstracts from the five invited speakers: Sean Eddy (HHMI's Janelia Farm, USA), Minoru Kanehisa (Kyoto University, Japan), Sang Yup Lee (KAIST, Korea), Hideyuki Okano (Keio University, Japan) and Mark Ragan (University of Queensland, Australia).